2017
DOI: 10.1186/s12944-017-0430-9
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of mitochondrial ATP synthase inhibitory factor 1 (IF1) in coronary heart disease: a literature review

Abstract: Cardiovascular disease (CVD) is the leading cause of death worldwide, and so the search for innovative and accurate biomarkers for guiding prevention, diagnosis, and treatment is a valuable clinical and economic endeavor. Due to a recent findings that the serum concentration of mitochondrial ATP synthase inhibitory factor 1 (IF1) is an independent prognostic factor in patients with coronary heart disease (CHD), we reviewed the role of this protein in myocardial ischemic preconditioning, its correlation to plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(76 reference statements)
0
6
0
1
Order By: Relevance
“…Adenosine triphosphate is considered as one of the most important indicators of assessing myocardial energy metabolism levels and EC reflects the general level of myocardial metabolism ( Maierean et al, 2017 ). As shown in Figure 1B , the peak plots of ATP, ADP, and AMP were effectively separated within 7.5 min.…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine triphosphate is considered as one of the most important indicators of assessing myocardial energy metabolism levels and EC reflects the general level of myocardial metabolism ( Maierean et al, 2017 ). As shown in Figure 1B , the peak plots of ATP, ADP, and AMP were effectively separated within 7.5 min.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the recovery of mitochondrial function, including the respiratory activity and ATP‐producing capacity, has been considered as a primary therapeutic target for improving the prognosis of patients with CAD 19 . Results from a recent study have suggested that the serum concentration of mitochondrial ATP synthase inhibitory factor 1 is independently negatively associated with all‐cause and cardiovascular mortality in patients with CAD 20 . Another study suggested that ectopic ATP synthase on endothelial cells could be a potential and novel therapeutic target for CAD 21 …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ATPase plays a role in ischemic preconditioning in the heart [23] and the brain [24]. The main factor regulating ATPase activity during preconditioning is suggested to be a protein called mitochondrial F0F1 ATPase inhibitory factor 1 (IF1), which inhibits ATP hydrolysis by ATPase [25]. This protein seems to be expressed in response to hypoxia-inducible factor 1α (HIF-1α) in liver and brain cells [24,26].…”
Section: Introductionmentioning
confidence: 99%